2022
DOI: 10.3389/fnut.2022.810827
|View full text |Cite
|
Sign up to set email alerts
|

Effects of PEF-Assisted Freeze-Drying on Protein Quality, Microstructure, and Digestibility in Chilean Abalone “Loco” (Concholepas concholepas) Mollusk

Abstract: The purpose of this study was to apply different pulsed electric field (PEF) conditions as a pretreatment to the freeze-drying (FD) process of Chilean abalone and to assess its effects on protein quality, microstructure, and digestibility of the freeze-dried product. The treatments PEF (0.5, 1.0, and 2.0 kV cm−1) and cooking (CO) were applied at 100°C × 15 min. Then, their performances were subjected to a FD process. PEF + CO pretreated freeze-dried samples showed shorter process times than freeze-dried contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…They also indicated that the temperature of 60 • C, which was also used in this research, gave the best outcome in terms of the PEF pretreatment beneficial effect of the parameters tested (50, 60, 70, 80 • C). On the contrary, the freeze-drying time reduction was consistent with previous studies [49]. Irrespective of the impact of the pretreatment, surprisingly, in this research, freeze-drying turned out to be a more effective solution to remove water from poultry meat samples.…”
Section: The Influence Of Pretreatment On the Kinetics Of The Hot Air...supporting
confidence: 91%
“…They also indicated that the temperature of 60 • C, which was also used in this research, gave the best outcome in terms of the PEF pretreatment beneficial effect of the parameters tested (50, 60, 70, 80 • C). On the contrary, the freeze-drying time reduction was consistent with previous studies [49]. Irrespective of the impact of the pretreatment, surprisingly, in this research, freeze-drying turned out to be a more effective solution to remove water from poultry meat samples.…”
Section: The Influence Of Pretreatment On the Kinetics Of The Hot Air...supporting
confidence: 91%
“…Abalone was also susceptible to disease and death during aquaculture, because of changes in water temperature and insufficient food supply. Abalone is now mainly processed into frozen, dried and canned products ( Palma-Acevedo et al, 2022 , Pizarro-Oteiza et al, 2023 ) to extend its shelf life and distribution range. With the advancement of aquaculture technology and innovation in abalone processing, the shelf life of abalone products has been increased, the scale of distribution has increased and the utilization of raw materials improved.…”
Section: Introductionmentioning
confidence: 99%
“…Such compounds are typically recovered by conventional extraction methods, which require large volumes of polluting and harmful solvents (e.g., hexane, acetone, and petroleum ether) and long maceration times (Parniakov et al, 2014). Recent efforts have explored the use of electrotechnologies as biomass pretreatments such as pulsed electric field (PEF) (Carullo et al, 2018;Genovese et al, 2021;Naliyadhara et al, 2022;Palma-Acevedo et al, 2022), high voltage electric field discharge (HVED) (Almohammed et al, 2017;El Kantar et al, 2019;Barišić et al, 2022), and ohmic heating (Kulshrestha et al, 2006;Moreno et al, 2012). All these technologies provoke mild cell disruption that weakens or ruptures cell sheaths to ultimately intensify the extractability of the targeted intracellular compounds without jeopardizing their original integrity (Barba et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…Within this framework, PEF and HVDE are distinguished among the other electrotechnologies due to their efficiency in the electroporation process (Barba et al, 2015b). The potential of pulsed electric field (PEF) technology to induce non-thermal membrane permeability in biological cells has been successfully demonstrated (Mahn et al, 2021;Palma-Acevedo et al, 2022;Tylewicz et al, 2022;Zhang et al, 2022). One application of PEF-assisted extraction is cold diffusion based on the rupture of the cell membrane when subjected to external PEF; this increases the electrical conductivity and permeability of the intracellular material (Naliyadhara et al, 2022;Sarkis et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%